EVALUASI PELAKSANAAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA SEHAT (PIS-PK) DI PUSKESMAS BESTARI KOTA MEDAN - dina lolita daulay; Ismail Efendi; Nuraini Nuraini (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
The Healthy Indonesia Program is one of the targets to be achieved in the 2015-2019 National Medium-Term Development Plan (RPJMN). Medan City Bestari Health Center has not yet reached the target of collecting family data because the commitment of healthy family advisors is lacking in conducting family data collection, data collection time is limited, residents are difficult to find, sometimes the builders of healthy families often do not meet residents at home, evaluation of data collection results has not been carried out periodically even though Puskesmas Bestari has socializing about the Healthy Indonesia Program with the Family Approach (PIS-PK) The research aims to evaluate the implementation of the Healthy Indonesia Program with the Family Approach (PIS-PK) at the Bestari Health Center in Medan City. This type of qualitative research is with a descriptive approach. The informants in this study were key informants were the Head of the Bestari Health Center in Medan City, the main informants were the Coordinator of PIS-PK, doctors and members of the healthy family data collection team consisting of Health Administration, Nutrition, Environmental Health and Midwives and triangulation informants were the Head of Public Health Division of Health Office Kota Medan. The sampling technique uses snowball sampling. Data analysis is performed by data reduction, data presentation and drawing conclusions. The results of the study are human resources trained in TOT-PIS-PKada 5 people and TOT management of puskesmas there are 2 people, insufficient funds available, inadequate facilities and infrastructure, PIS-PK implementation policy for SK Head of Puskesmas, socialization of Permenkes No. 39 2016 has been implemented but there is no roadmap, planning according to the program, organizing the family development team is not in accordance with Permenkes Number 39 of 2016, family data collection is carried out but there are still families living in hard to find homes, there are often delays in reporting and the healthy family index at the puskesmas level has not reached 60% of the target 100 % in July 2019 It is recommended that health centers can overcome the problems that exist in the data collection ranging from input to the output of a healthy family index can be achieved